Roughness and bearing analysis of ZnO nanorods - Kaya, S.; Ozturk, O.; Arda, L. (Elsevier BV, 2020)
Abstract It is essential to analyze the surfaces of thin films precisely to control the production process and the performance of nano-scale devices. Conventional techniques give limited information about the nano-scale surface morphology. Instead, atomic force microscopy (AFM) provides more accurate results about the surface parameters of nanostructures. Hence, in the current study, two-dimensional (2D) and three-dimensional (3D) morphological properties of zinc oxide (ZnO) nanorods (NRs) were investigated using AFM. ZnO NRs were produced via a hydrothermal method at different growth times and temperatures. The surface texture was also examined by scanning electron microscopy (SEM). The results revealed that the morphological parameters such as diameter, length, and shape of the nanorods could be tuned by changing growth time and temperature. Moreover, we analyzed the most crucial roughness and bearing analysis parameters, which affect the functional properties of ZnO in the surface engineering applications. The average roughness increased from 5.86 nm to 17.30 nm as growth time increased from 2 h to 5 h. The average roughness was obtained as 10.92 nm for the temperature of 90 °C and it reached 41.13 nm for 150 °C. In addition, height distribution and bearing area curves associated with the real contact area were reported. 90% of the area was spread at a depth of 48 nm for the growth time of 2 h while this value was obtained 183 nm for 5 h Addition, 90% of the area was spread at a depth of 88 nm and 457 nm for the temperature of 90 °C and 150 °C, respectively. We believe that our study would be a pioneering perspective on bearing analysis of ZnO nanorods.